1988
DOI: 10.1126/science.242.4880.908
|View full text |Cite
|
Sign up to set email alerts
|

The Surface Temperature of the Sun and Changes in the Solar Constant

Abstract: The solar distortion telescope has been used to measure the limb shape and latitude dependence of the limb brightness during the summer months for a 5-year period-a time base sufficient to detect solar cycle trends in the data. Comparison of these observations with spaceborne measurements of the solar constant suggests that a significant part of the solar cycle variation in irradiance is a result of temporal changes in the latitude-dependent surface temperature of the sun. P RECISE SPACEBORNE MEASUREments of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
76
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(80 citation statements)
references
References 16 publications
3
76
1
Order By: Relevance
“…In the synoptic map mentioned above, there is no trace of magnetic activity visible in the active belts in 2009; moreover, our results show that the granulation is not perturbed in these latitudes. Consequently, if at this phase of minimum of activity some strong magnetic field is embedded deep in the convection zone, the structure of the atmosphere close to the surface is not perturbed, which is in disagreement with the predictions of several theoretical works (Parker 1987(Parker , 1995Kuhn 1988Kuhn , 1993Kuhn et al 1988;Goode & Kuhn 1990). Therefore, the magnetic field (neither the quiet Sun magnetic field nor the strong magnetic field in active regions) is probably not the cause of the latitude variation of the solar granulation in the period of minimum of activity reported in this paper.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…In the synoptic map mentioned above, there is no trace of magnetic activity visible in the active belts in 2009; moreover, our results show that the granulation is not perturbed in these latitudes. Consequently, if at this phase of minimum of activity some strong magnetic field is embedded deep in the convection zone, the structure of the atmosphere close to the surface is not perturbed, which is in disagreement with the predictions of several theoretical works (Parker 1987(Parker , 1995Kuhn 1988Kuhn , 1993Kuhn et al 1988;Goode & Kuhn 1990). Therefore, the magnetic field (neither the quiet Sun magnetic field nor the strong magnetic field in active regions) is probably not the cause of the latitude variation of the solar granulation in the period of minimum of activity reported in this paper.…”
mentioning
confidence: 55%
“…Previously, Kuhn et al (1988) also suggested that a latitudinal temperature distribution characterized by large-scale quadrupolar variations could be related to the solar differential rotation. Then the question arises about the cause of the perturbation which occurs around 60 • .…”
mentioning
confidence: 96%
“…Summary of total solar irradiance measurements total irradiance, which is not explained by the effect of sunspots, faculae, and the magnetic network, is a difficult problem since global effects may also produce variations in total irradiance. It has been shown that changes in the differential rotation in the interior of the Sun, the solar dynamo magnetic field near the base of the convective zone (Kuhn 1996, photospheric temperature changes (Kuhn et al 1988), large scale missing flows or large scale convective cells (Ribes et al 1985;Fox & Sofia 1994) and/or radius changes (Delache et al 1985;Ulrich & Bertello 1995;Kuhn et al 1985Kuhn et al , 1988Godier & Rozelot 2000) may also contribute to irradiance variations. Therefore, simultaneous studies of total irradiance and solar global parameters are essential to better understand the underlying physical mechanism of irradiance changes and to predict solar-induced climate changes.…”
Section: Description Of the Total Irradiance Measurementsmentioning
confidence: 99%
“…Kroll et al (1990) and Kroll & Hill (1991) used the Santa Catalina Laboratory for Experimental Relativity by Astrometry (SCLERA) telescope to fit changes in limb darkening, associated with solar activity, to variations in the solar irradiance. and Kuhn et al (1988) have fit measurements of latitudinal fluctuations in photospheric temperature near the solar limb, obtained from the Princeton Distortion Telescope (PDT), to variations in the ACRIM I total irradiance. Kuhn et al (1988) have been able to obtain fits to total irradiance measurements from satellites with high correlations.…”
Section: Def = '£^-mentioning
confidence: 99%
“…and Kuhn et al (1988) have fit measurements of latitudinal fluctuations in photospheric temperature near the solar limb, obtained from the Princeton Distortion Telescope (PDT), to variations in the ACRIM I total irradiance. Kuhn et al (1988) have been able to obtain fits to total irradiance measurements from satellites with high correlations. Kroll et al (1990), on the other hand, have found evidence for a change in the limb darkening that is not like the solar cycle.…”
Section: Def = '£^-mentioning
confidence: 99%